Trend factors around the world: Performance and determinants - Han, Yufeng; Mo, Xi Nancy; Yang, Jian (Journal of Banking & Finance, 2025)
This study investigates the performance of trend factors across different markets around the world and demonstrates that the trend factors perform well across most of developed markets and many emerging markets, outperforming the market portfolio, short-term reversal, momentum, and long-term reversal. We further examine how cultural and legal differences influence the performance of the trend factor trading strategy and find it is more profitable in countries where the individualism is higher and securities laws are better enforced. Finally, the global trend factor aggregating individual market trend factors performs well and explains various global portfolios’ returns. The findings suggest that the trend factors present a challenge to traditional risk-based asset pricing theories, and trend factor trading strategies may deserve more attention in international portfolio management.